(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this study one handered and five samples were collected from skin infection in hospital Diwaniyah Dermatology Consultancy in Al-Diwaniyah governorate. from December 2018 to April 2019. All samples were cultured and Identified by using phenotyping tests. The results revealed that 41 isolates were Staph. spp. and 30 Isolates out of them Diagnosed Staphylococcus aureus by using (API staph). Virulence factors were explicated by using polymerase chain reaction (PCR) methicillin-resistant staphylococcus aureus ( MRSA ), were identified by detecting (mecA gene), which revealed that all skin infections were MRSA ( 100 % ). Also, toxic shock syndrome toxin ( TSST ) were identified by using PCR to detect ( tst-1 gene 326 bp.), which revealed that 23 isolate were positive out of 30 isolate ( 76.33 % ).